Extraction of crude polysaccharides from Duchesnea indica (Andrews) Focke: optimization by response surface methodology. Issue 8 (3rd August 2015) - Chen, Jing; Sun, Chao; Han, Liang; Lin, Xi; Wang, Li; Shen, Minna; Yu, Fei; Chen, Jianhua
Abstract: A full set of optimization procedure was applied to the extraction of anti-viral polysaccharides from Duchesnea indica (Andrews) Focke. By Plackett–Burman factorial design, three parameters (extraction time, extraction temperature, and ratio of water to raw material) were identified as significant to the extraction yield. However, no significant parameters had been identified for antiviral activity. A three-level-three-factor Box–Behnken factorial design was then employed to further optimize the extraction condition. The experimental data were fitted to a second-order polynomial equation using multiple regression analysis and also examined using appropriate statistical methods. This led to the construction of a response surface indicating the optimal values for each parameter and response studied. Concerning the extraction yield, an extraction at 98.51 ºC for 6.16 h with a ratio of water to raw material of 30.94 mL/g was found to be optimal. Under the optimized conditions, the experimental yield was 6.430 ± 0.078%, which was well matched with the predicted yield of 6.509%. Graphical abstract: : Extraction of anti-viral polysaccharides from Duchesnea indica (Andrews) Focke is optimized by response surface methodology.